On the hydrodynamics of bobbing cones - Drake, K; Taylor, R; Taylor, P; Bai, W (Elsevier, 2009)
The paper describes an experimental investigation into the hydrodynamics of a right circular cone undergoing transient forced vertical oscillations in otherwise still water. Attention is given to the vertical fluid force and the relative vertical motion between the cone and its intersection with the adjacent free water surface. Comparisons are made between linear theory and experimental results extracted from paired response time histories obtained with input displacements of opposite sign. Comparisons are also made with the predictions obtained from fully non-linear numerical models. A slowly varying setup is observed in the measured relative vertical motion and a new second order term is identified in order to formulate a theoretical explanation.